Design and Build a Robusta Coffee Shop Information System as a Website-Based Transaction and Promotion Media (Case Study: Kite Robusta Coffee Shop Pagar Alam - Putri Aprilia; Kemas Muhammad Wahyu Hidayat (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Mosques play a central role in Muslim community life, not only as places of worship but also as centers for social and financial activities such as donations, alms management, and information dissemination. However, in the current era of rapid technological development, many mosques still rely on manual systems for financial management and communication. This condition often leads to recording errors, calculation inaccuracies, data loss, limited access to information, and reduced transparency, which can affect public trust in mosque management. Therefore, innovation in the form of information technology is needed to support more effective, accurate, and transparent mosque administration. This research aims to assist the management of Raudhatul Mukhlisin Mosque in improving the efficiency and accuracy of mosque financial data management through the development of a website-based information system. The system was developed using the Waterfall method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. This study employed qualitative research methods with data collection techniques including observation and literature review. The system was built using PHP, HTML, and MySQL, and tested using the Black Box method. The results indicate that the system facilitates financial data processing, reporting, and information access, while increasing transparency and accountability for mosque administrators and worshippers.